2020
DOI: 10.1096/fj.201901318r
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine exacerbates cognitive dysfunction associated with cerebrovascular pathology

Abstract: Abbreviations: [Ca 2+ ] i , intracellular calcium ion; • O − 2 , superoxide anion; AD, Alzheimer's disease; ADMA, asymmetric dimethylarginine; Aβ, amyloid-β peptide; BBB, blood-brain barrier; hBMVEC, human brain microvessel endothelial cell; DAPI, 4′,6-diamidino-2-phenylindole, dihydrochloride; EB, Evans blue; eNOS, endothelial nitric oxide synthase; GFAP, glial fibrillary acidic protein; GSH, glutathione; GSNO, S-nitrosoglutathione; Iba-1, ionized calcium-binding adaptor molecule 1; L-NIO, N 5 -(1-Iminoethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Our laboratory has recently reported that ADMA induces endothelial/vascular dysfunction by interacting with VEGF [33]. Based on these studies, we analysed blood levels of ADMA and VEGF in EAE mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our laboratory has recently reported that ADMA induces endothelial/vascular dysfunction by interacting with VEGF [33]. Based on these studies, we analysed blood levels of ADMA and VEGF in EAE mice.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated the effect of ADMA overburden on clinical EAE disease. Recently, we have reported that systemic treatment of C57BL/6 mice with a daily dose of ADMA (50mg/kg/day/ip) increases the levels of ADMA in the blood [33]. Based on these data, we treated EAE mice with the same daily dose of ADMA starting on the day of disease onset (day 11 post‐immunization).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A loss-of-function Ddah1 promoter polymorphism is associated with increased susceptibility to cardiovascular diseases and thrombosis stroke 12 . Thus, these SNPs of Ddah1 are likely associated with metabolic syndrome including metabolic bone diseases 13 , 14 . Therefore, our initial aim was to investigate if the loss-of-function Ddah1 promoter polymorphism is associated with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%